Effects of hydroxyapatite gypsum puger scaffold applied to rat alveolar bone sockets on osteoclasts, osteoblasts and the trabecular bone area - Amiyatun Naini; I Ketut Sudiana; Mohammad Rubianto; Utari Kresnoadi; Faurier Dzar Eljabbar Latief (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Damage to bone tissue resulting from tooth extraction will cause alveolar bone resorption. Therefore, a material for preserving alveolar sockets capable of maintaining bone is required. Hydroxyapatite Gypsum Puger (HAGP) is a bio-ceramic material that can be used as an alternative material for alveolar socket preservation. The porous and rough surface of HAGP renders it a good medium for osteoblast cells to penetrate and attach themselves to. In general, bone mass is regulated through a remodeling process consisting of two phases, namely; bone formation by osteoblasts and bone resorption by osteoclasts. Purpose: This research aims to identify the effects of HAGP scaffold application on the number of osteoblasts and osteoclasts, as well as on the width of trabecular bone area in the alveolar sockets of rats. Methods: This research used Posttest Only Control Group Design. There were three research groups, namely: a group with 2.5% HAGP scaffold, a group with 5% HAGP scaffold and a group with 10% HAGP scaffold. The number of samples in each group was six. HAGP scaffold at concentrations of 2.5%, 5% and 10% was then mixed with PEG (Polyethylene Glycol). The Wistar rats were anesthetized intra-muscularly with 100 mg/ml of ketamine and 20 mg/ml of xylazine base at a ratio of 1:1 with a dose of 0.08-0.2 ml/kgBB. Extraction of the left mandibular incisor was performed before 0.1 ml preservation of HAGP scaffold + PEG material was introduced into the extraction sockets and suturing was performed. 7 days after preparation of the rat bone tissue, an Hematoxilin Eosin staining process was conducted in order that observation under a microscope could be performed. Results: There were significant differences in both the number of osteoclasts and osteoblasts between the 2.5% HAGP group, the 5% HAGP group and the 10% HAGP group (p = 0.000). Similarly, significant differences in the width of the trabecular bone area existed between the 5% HAGP group and the 10% HAGP group, as well as between the 2.5% HAGP group and the 10% HAGP group (p=0.000). In contrast, there was no significant difference in the width of the trabecular bone area between the 2.5% HAGP group and the 5% HAGP group. Conclusion: The application of HAGP scaffold can reduce osteoclasts, increase osteoblasts and extend the trabecular area in the alveolar bone sockets of rats.